CAN THE COLLAPSE OF THE TRADE SYSTEM UNDER THE WORLD TRADE ORGANIZATION BE PREVENTED? - Sanja Jelisavac Trošić (PEOPLE: International Journal of Social Sciences, 2025)
The World Trade Organization (WTO) was formed as a much-needed organization that will deal with trade issues and form binding rules for international trade. But today, in many discussions, the question is raised, is the WTO still relevant? The rules-based multilateral trading system has been around for so long that countries, companies, and consumers largely take it for granted. These rules are essential for ensuring trust in a stable and predictable trading environment. The aim of the research is to determine the extent to which the existing system of global trade regulation has collapsed and to what extent it is possible to recover, modernize and make it functional for the needs of WTO member countries. We will pay attention to the various interests of powerful and rich countries, emerging economies, large and small countries, as well as poor and underdeveloped countries. In the analysis, we take into account the pros and cons of maintaining the current WTO system, as well as the proposals for reform and sustainable development of this international organization. We will give a critical review of international trade regulation through the WTO system, which is currently changing and trying to justify its status and results. The current state of the WTO is a matter of general interest and it is important that all member countries engage in recovery, regardless of the issues and how different their views are. This paper should contribute to the ongoing discourse and provide materials for the future discussions on the topic of WTO survival and reform.